Hubungan Gaya Kepemimpinan dan Komunikasi Kepala Sekolah dengan Produktivitas Guru Honorer Madrasah Ibtidaiyah Negeri 05 Labuhan Batau dalam Konteks Pendidikan Islam - Hajjatul Maria Ulfa; Wahyu Nur; Adolina Siregar; Messiono Messiono; Toni Nasution (UIN Fatmawati Sukarno Bengkulu, 2023)
This research was conducted to know and explain in detail about communication style of the principal public school MIN 5 Labuhan Batu regency to provide work motivation of the honorary teacher. The sub-focus used is physical condition, role, language, relationships and constraints. This research approach was qualitative with descriptive methods. The selection of informants obtained through purposive sampling technique, 1 (one) key informant and 6 (six) supporting informants. Data collection thechniques were attained throug non-participant observation, in-depth interviews documentation, library studies, and internet searching. The data analysis used is data collection, data reduction, data display and conclusion drawing. The result showed that the physical condition of the principal to provide work motivation of the honorary teacher didn’t have a negative impact on the communication process. The role of the principal to provide work motivation of the honorary teacher had a multifunctional roles, can play a role as leader, co-worker, friend, and role as their parent. The language used by the principal to provide work motivation of the honorary teachers was Bahasa Indonesia and Sundanese language. The relationship between school principal and honorary teachers was very close. The constrains for school principal to provide work motivation to honorary teachers was related with delegation or gave a sudden assignments without any clue. The conclusion of this research are equalitarian style,, and had an open style, relaxed, animated, and friendly.